Annual Plan 1972-73 Mysore - Planning Commission (Planning Commission, 1971)
The Sarasvati Project consisting of two units - estimated at Rs. 5271.80 lakhs, was completed and these two units of an installed capacity of 1, 78, 200 kW. Was commissioned in the Third Plan period. The expenditure incurred to end of March, 1971 Is Rs.4, 877-59 lakhs. Expenditure anticipated in 1971-72 is Rs.10.00 lakhs. A sum of Rs.4-00 lakhs has been provided for 1972-75 to meet certain adjustment transactions. The total provision made during the Fourth Plan period is Rs.170.00 lakhs. Sharavathi Project - Stage II This stage consists of six generating units of 89,100 kW each. The estimated cost is Rs.5965-86 lakhs. So far, five units have been commissioned and are in service and the installation of sixth unit has been completed and the unit test charged on 51-5-71- is expected to be pressed into service by end of October,' 1971- The total expenditure to end of 1970-71 Is Rs.5.526.89 lakhs. The anticipated expenditure during 1971-72 is in the order of Rs. 100.00 lakhs and the provision for 1972-75 proposed is Rs.50.00 lakhs. The total prevision for the Fourth Plan period is Rs.907-00 lakhs.
Government of Mysore
Government of Mysore
Keywords: Tungabhadra Hydro-Electric Project Left Banks; Kalinadi Hydro-Electric Projects; Transmission Lines Stage; Works for Irrigation Department for providing Power Houses; Cauvery Valley Power Development; Centrally Sponsored Schemes; Inter-State Transmission line between Hanrpi and Munirabad; Labour requirements during the construction phases